Responsibility and Justice in Aristotle’s Non-Voluntary and Mixed Actions - Campos, Andre Santos (Journal of Ancient Philosophy, 2013)
Aristotle develops his theory of moral responsibility mainly in part III of the Nicomachean Ethics, where he claims we are held responsible for our voluntary actions and thus liable to either praise or blame, whereas for our involuntary actions we may be liable to either pardon or pity. However, he recognizes how difficult it is to present general criteria allowing a clear-cut distinction between voluntary and involuntary actions. That is why he presents two other types of action that are somehow in-between voluntariness and involuntariness: non-voluntary and mixed actions. Notwithstanding, he fails to state exactly what should be the appropriate response to such moral actions. In this article, the author tries to show that the only way to effectively make sense of moral responsibility in non-voluntary and in mixed actions is to consider the ensemble of praise, blame, pardon and pity as constituting not two pairs of alternative responses to voluntary and involuntary actions, respectively, but rather one single scale in different degrees of the same kind of moral responsibility – with praise at the top, pity at the bottom, and several grey areas in-between. Moral responsibility in non-voluntary and mixed actions is set in those grey areas.